GEN-Z SEHAT (Gerakan Edukasi Gizi, PHBS untuk Sehat Anak dan Keluarga di Desa) - Januarista, Afrina; Rahmita, Lisa; Fadila, Nur; Abdullah, Ardiansya A; Maliha, Dhya Nazwa; Lamang, Nurmawati; Sinaga, Enjelina; Tiadora, Ni Nyoman Nick; Indriyani, Indriyani; Sihombing, Jovanca Estevania Lynch; Gana, Patrisia Maura; Rezal, Mohammad; Huntala, Noval; Marcelina, Andina; Sapari, Anisa Adianti (Sasambo: Jurnal Abdimas (Journal of Community Service), 2025)
Program pengabdian masyarakat ini bertujuan meningkatkan kesadaran gizi seimbang dan perilaku hidup bersih sehat (PHBS) pada anak sekolah dasar di Desa Ganti. Permasalahan utama adalah rendahnya pemahaman anak terhadap pentingnya gizi dan kebersihan diri. Melalui program GEN-Z SEHAT (Gerakan Edukasi Gizi, PHBS untuk Sehat Anak dan Keluarga di Desa) dilakukan sosialisasi, demonstrasi kebersihan tangan, dan pendampingan pembiasaan hidup sehat. Hasil evaluasi menunjukkan peningkatan pemahaman dan perilaku anak dalam menerapkan PHBS serta kebiasaan makan bergizi, dengan nilai rata-rata berada pada kategori baik, yang sekaligus berkontribusi terhadap pencapaian tujuan SDGs nomor 3 tentang kesehatan yang baik dan kesejahteraan, serta memiliki potensi keberlanjutan melalui pembiasaan perilaku sehat di lingkungan sekolah.  Program ini menyimpulkan bahwa edukasi interaktif berbasis pendampingan efektif menumbuhkan perilaku sehat anak sekolah di lingkungan pedesaan. GEN-Z SEHAT: Nutrition and CHLB Education Movement for Healthy Children and Families in Rural Areas This community service program aims to increase awareness of balanced nutrition and clean and healthy living behavior (PHBS) among elementary school students in Ganti Village. The main issue identified is the low level of children’s understanding of the importance of nutrition and personal hygiene. Through the GEN-Z SEHAT Program (Nutrition and PHBS Education Movement for Healthy Children and Families in the Village), activities included socialization sessions, hand hygiene demonstrations, and mentoring to develop healthy lifestyle habits. Evaluation results showed an improvement in students’ understanding and behavior in practicing PHBS and healthy eating habits, with average scores categorized as good. This outcome contributes to the achievement of SDG Goal 3: Good Health and Well-being, and demonstrates sustainability potential through the habituation of healthy behaviors within the school environment. The program concludes that interactive, mentoring-based education is effective in fostering healthy behaviors among elementary school children in rural areas.